PERSEPSI AKUNTAN MENGENAI DAMPAK ARTIFICIAL INTELLIGENCE PADA PROFESI AKUNTAN PUBLIK (Studi Kasus pada Kantor Akuntan Publik Drs. Syamsul Bahri , MM., AK., & Rekan) - Gultom, Theresia Febri Yanti; Hutapea , Herti Diana; Siboro , Danri Toni (JURNAL LENTERA AKUNTANSI, 2024)
This study aims to analyze the perceptions of public accountants regarding the impact of AI on their profession, using a case study at Kantor Akuntan Publik (KAP) Drs. Syamsul Bahri, MM., AK., & Rekan. This research employs a descriptive quantitative method. The population in this study consists of 30 accountants working at KAP Drs. Syamsul Bahri, MM., AK., & Rekan. From this population, 15 respondents were selected using the purposive sampling technique. The findings indicate that the knowledge aspect of accountants regarding AI falls into the good category (69%), demonstrating a strong understanding of AI’s role in accounting. The awareness aspect is categorized as moderate (61%), indicating that accountants recognize the importance of AI in their profession, although there is still variation in their perspectives on its long-term impact. Meanwhile, the skills aspect received the highest score in the good category (81%), suggesting that public accountants at KAP Drs. Syamsul Bahri, MM., AK., & Rekan have developed sufficient competencies in utilizing AI technology to support their work